Lethal Experimental Tick-Borne Encephalitis Infection: Influence of Two Strains with Similar Virulence on the Immune Response - Shevtsova, Anastasia S.; Motuzova, Oxana V.; Kuragina, Vera M.; Akhmatova, Nelli K.; Gmyl, Larissa V.; Kondrat'eva, Yaroslava I.; Kozlovskaya, Liubov I.; Rogova, Yulia V.; Litov, Alexander G.; Romanova, Lidiya Iu.; Karganova, Galina G. (Frontiers in Microbiology, 2017)
Tick-borne encephalitis virus (TBEV) is a tick-transmitted arbovirus that causes serious diseases in humans in Europe and Northern Asia. About 6,000-10,000 cases are registered annually, and one-third of them lead to sequela with different degrees of severity. Two TBEV strains (Absettarov and EK-328) similar in virulence rate in laboratory mice were used to study pathogenesis and immune response upon lethal infection in mice. The strains differed in the dynamics of appearance of virus, IFNs and other cytokines in blood of mice, and ability to induce a cytokine storm in the terminal stages of disease and a non-sterile immunity. Moreover, the TBEV strains differed in characteristics of their interactions with DCs: level of reproduction in these cells, virus dose triggering IFN-α production, and impact on DCs’ maturation. Infection of DCs with Absettarov strain led to IFN-α induction only at high multiplicity of infection (MOI), and an increased amount of the mature DCs with high adhesion activity and low-level of MHCII positive cells. While reproduction of the EK-328 strain in DCs was less efficient, a low dose of the virus induced IFN-α production and stimulated maturation of DCs with relatively low adhesive capacity, but with the high percentage of cells expressing MHCII molecules. Thus, the studied strains differed significantly in the impact on DCs’ maturation and antigen presentation to CD4+ lymphocytes. Injection of low (103 PFU) and high (106 PFU) doses of both TBEV strains caused a lethal infection in mice. At the same time, the dose of the virus in the inoculum, regardless of the strain properties, affected the following virulence characteristics: the time of virus appearance in brain (day 4-5 p.i. vs day 1 p.i.), time of IFN appearance in blood (10 h p.i. vs 5 h p.i.), concentration of IFN-α in blood, and induction of IFN-α during infection of DCs. Therefore, virulent TBEV strains during lethal infection can interact differently with the host immune system, and the infectious dose has an impact on both: virus spread in the infected organism and immune response activation.